Assessment of Night Sky Quality in Ganten Village, Kerjo District, Karanganyar: A Prospective Evaluation for the Establishment of the Falak Observatory - Delta Rosiana; Yudhiakto Pramudya; Okimustava Okimustava; Muchlas Muchlas (University of Muhammadiyah Sumatera Utara, 2023)
The establishment of an astronomical observatory requires a thorough evaluation of meteorological parameters and Night Sky Brightness Levels (NSBL). This research focuses on assessing the potential of Karanganyar as a site for astronomical education and new moon observations. To determine the NSBL in Karanganyar, satellite imagery was used, indicating favourable conditions. However, NSBL can be affected by light pollution and moon phases in specific locations. To complement the satellite data, additional measurements were taken using a Sky Quality Meter (SQM). The SQM values were processed using probability distribution analysis and showed a highest probability NSBL value of 17.22 mag/arsec2, while the maximum NSBL value reached 20.99 mag/arsec2. The NSBL derived from satellite data was 21.47 mag/arsec2. Our study shows that Karanganyar has predominantly high NSBL, suggesting low light pollution and excellent sky clarity in the region.